The Impact of Liquidity and Profitability on Shareholders’ Equity: Evidence from the Iraqi Stock Exchange - Sangawi, Shakhawan Saeed; Salih, Kaiwan Hasan; Ahmad, Kadhm Kamal (Journal of Islamic Economics and Finance Studies, 2025)
Despite the extensive body of research on shareholder value in equilibrium markets, the relationship between liquidity, earnings volatility, and shareholder returns in the Iraqi Stock Exchange remains understudied. This market is characterized by economic sanctions, currency fluctuations, and sectoral imbalances. To address this research gap, this study investigates the impact of liquidity and earnings on shareholders’ equity, focusing on manufacturing companies listed on the Iraqi Stock Exchange during the period 2018–2022. A quantitative research design was employed, utilizing purposive sampling to select 10 Iraqi manufacturing companies whose annual audited financial statements were publicly available on the stock exchange. The analysis was conducted using panel multiple linear regression (EGLS) in EViews 12. The findings reveal that working capital management has a significant positive effect on shareholders’ equity. This suggests that effective working capital management can enhance shareholder value by improving profitability, liquidity, and operational efficiency, thereby increasing the firm’s overall value. Conversely, the study finds that profit does not have a significant impact on shareholders’ equity, indicating that short-term liquidity efficiency may exert a more immediate influence on stock performance than profitability levels. Moreover, the current ratio shows a significant positive effect on shareholders’ equity, which may reflect excessive liquidity resulting from overinvestment in unprofitable or idle assets—an effect that could potentially reverse in the future. The research model explains 93.86% of the variance in shareholders’ equity as accounted for by the independent variables. In conclusion, this study provides a comprehensive understanding of the financial management strategies and techniques that influence shareholder value in emerging and volatile markets such as Iraq.